Portugal : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Portugal achieved progress in containing the fiscal deficit, strengthening financial sector resilience, and structural reforms. Executive Directors commended the efforts to contain the fiscal deficit in line with the requirements of the Stability and Growth Pact. They encouraged the authorities to implement the recommendations of the fiscal Report on the Observance of Standards and Codes (ROSC) and to move toward comprehensive multiyear budget targets. They underscored that a sustainable economic recovery hinges on strengthening competitiveness and on coping with the effects of euro appreciation.